Fiscal Policies to Counter Climate Change and Economic Depression in the Post Covid-19 European Union - Anastasakis, Nikolaos (HAPSc Policy Briefs Series, 2020)
The Covid-19 health crisis will eventually fade out, but the consequential economic crisis is right ahead of us, along with the ongoing climate crisis. The European Union’s policies and institutions seem to hinder the green transition, in favor of fiscal balance and debt repayment among its member states. This paper proposes some fiscal policies, such as an EU “Employer of Last Resort” (ELR) program, which could successfully counter the upcoming depression and climate change, to finally bring economic and social prosperity to the EU’s citizens.